JD6 - The Connection between Radio Properties and High Energy Emission in AGNs. (5th March 2015) - Giovannini, Gabriele; Cheung, Teddy
Abstract: While observations in the radio band are providing essential information on the innermost structures of relativistic jets in active galactic nuclei (AGN), the recent detection by Fermi of gamma-ray emission from many hundreds of blazars shows that the maximum jet power is emitted at high energies. Multi-wavelength monitoring observations further allow variability studies of the AGN spectral energy distributions over 13 orders of magnitude in frequency. The Joint Discussion offered the possibility for a comprehensive discussion of advances in the observational domain and stimulated theoretical discussion about our current understanding of jet physics.